SISTEM AKUNTANSI PENGELUARAN KAS PADA PT PRATAMA MITRA SEJATI JAKARTA - Maria Evy Purwitasari; Novita Eliza (POLITEKNIK LP3I JAKARTA, 2024)
A company implements an internal control system to support running its business. The application of the accounting system is applied according to the situation faced in assisting the company in providing the data and information needed by management in making decisions, carrying out supervision and operating the company efficiently. One system that requires extra supervision is cash. Cash requires special attention, because it is easily transferable and ownership cannot be proven, therefore internal control over cash disbursements is required. The formulation of the problem put forward in this paper is about the accounting system for cash disbursements at PT Pratama Mitra Sejati Jakarta. This research aims to determine the accounting information system, especially the existing cash receipts system of PT. Pratama Mitra Sejati Jakarta with the company's theory and SOP. This research uses qualitative research using data collection techniques and literature and field studies by means of observation and interviews. The results of the research carried out can be concluded that PT. Pratama Mitra Sejati Jakarta has a fairly good Cash Disbursement Accounting System.